Characterization of adenoviral transduction profile in prostate cancer cells and normal prostate tissue. Issue 12 (20th July 2017) - Ai, Jianzhong; Tai, Phillip W.L.; Lu, Yi; Li, Jia; Ma, Hong; Su, Qin; Wei, Qiang; Li, Hong; Gao, Guangping
Abstract : Background: Prostate diseases are common in males worldwide with high morbidity. Gene therapy is an attractive therapeutic strategy for prostate diseases, however, it is currently underdeveloped. As well known, adeno virus (Ad) is the most widely used gene therapy vector. The aims of this study are to explore transduction efficiency of Ad in prostate cancer cells and normal prostate tissue, thus further providing guidance for future prostate pathophysiological studies and therapeutic development of prostate diseases. Methods: We produced Ad expressing enhanced green fluorescence protein (EGFP), and characterized the transduction efficiency of Ad in both human and mouse prostate cancer cell lines in vitro, as well as prostate tumor xenograft, and wild‐type mouse prostate tissue in vivo. Ad transduction efficiency was determined by EGFP fluorescence using microscopy and flow cytometry. Cell type‐specific transduction was examined by immunofluorescence staining of cell markers. Results: Our data showed that Ad efficiently transduced human and mouse prostate cancer cells in vitro in a dose dependent manner. Following intratumoral and intraprostate injection, Ad could efficiently transduce prostate tumor xenograft and the major prostatic cell types in vivo, respectively. Conclusions: Our findings suggest that Ad can efficiently transduce prostate tumor cells in vitro as well as xenograft and normal prostate tissue in vivo, and further indicate that Ad could be a potentially powerful toolbox for future gene therapy of prostate diseases.